The exosomes of trypanosomes and other protists - Clayton, Christine; Estévez, Antonio M. (RNA Exosome, 2010)
The archaeal exosome contains three heterodimeric RNase PH subunits, forming a hexamer with RNase activity; on top sits a trimer of two different SI domain proteins. In animals and yeast, six different, but related subunits form the RNase PH-like core, but these lack enzyme activity; there are three different Si-domain proteins and enzyme activity is provided by the endo/exonuc lease Rrp44 or—mainly in the nuclear exosome—the Rnase D enzyme Rrp6. Trypanosomes diverged from yeast and mammals very early in eukaryotic evolution. The trypanosome exosome is similar in subunit composition to the human exosome, but instead of being an optional component, trypanosome RRP6 is present in the nucleus and cytoplasm and is required for exosome stability. As in human cells and yeast, the trypanosome exosome has been shown to be required for processing and quality control of rRNA and to be involved in mRNA degradation. Electron microscopy results for a Leishmania exosome suggest that RRP6 is located on the side of the RnasePH ring, interacting with several exosome core proteins. Results of a search for exosome subunits in the genomes of widely diverged protists revealed varied exosome complexity; the Giardia exosome may be as simple as that of Archaea.